Shiloh season - Naylor, Phyllis Reynolds (New York, NY : Aladdin Paperbacks, 1996)
When mean and angry Judd, who has never known kindness, takes to drinking and mistreats his dogs, Marty discovers how deep a hurt can go and how long it takes to heal.
Sequel to : Shiloh.
Ar
Keywords: Dogs -- Juvenile fiction; Kindness -- Juvenile fiction; West Virginia -- Juvenile fiction; Dogs; West Virginia; Fiction